Pengaruh Pemberdayaan terhadap Kelelahan Kerja dan Kecerdasan Emosional Perawat dan Bidan pada Rumah Sakit Palopo, Parepare dan Bone di Sulawesi Selatan - Roslina Alam; Armanu Thoyib (Jurnal Aplikasi Manajemen, 2010)
This study was conducted on nurses and midwives in Palopo, Bone, Parepare hospital in South Sulawesi. The focus of this research is on the sense of empowerment felt by nurses and midwives in relation to role ambiguity, burnout and emotional intelligence and the impact of role ambiguity on burnout and their impact on emotional intelligence. The number of sample is rounded to 85 people. The result of this research shows that: (1) empowerment has a positive and significant impact on role ambiguity, where empowered nurses and midwives still expuience role ambiguity (2) role ambiguity have positive and significant impact on burnout, (3) empowerment does not have significant impact on burnout, and (4) burnout does not have significant impact on emotional intelligence of the nurses and midwives.